Neutrophil-to-lymphocyte ratio as prognostic marker in esophageal cancer: a systematic review and meta-analysis - Pirozzolo, Giovanni; Gisbertz, Suzanne S.; Castoro, Carlo; van Berge Henegouwen, Mark Ivo; Scarpa, Marco (Journal of Thoracic Disease, 2019)
A high preoperative neutrophil-lymphocyte ratio (NLR) has been shown in several studies as a predictor of worse survival in many solid neoplasms, including esophageal cancer, but its impact remains unclear. The goal of this systematic review was to gain all the evidence about NLR in order to analyse its potential in predicting survival in esophageal cancer. Therefore, we conducted a systematic literature search of all relevant studies reporting data on NLR as prognostic marker in esophageal cancer patients. We considered overall survival (OS) as primary outcome, disease-free survival (DFS) and progression-free survival (PFS) as secondary outcomes. We included studies with a directly or indirectly available hazard ratio (HR), furthermore we used both fixed effect model and random effect model depending on heterogeneity. We included a total of 20 studies, published between 2011 and 2017, consisting of 6,457 patients. The NLR cut-off value ranges from 1.7 to 5. The HR for OS of all included studies was 1.60. The HR for DFS and PFS was 1.75 and 1.66 respectively. The survival sub-analysis about tumor characteristics, treatment modality, blood sample timing also confirmed NLR prognostic relevance with statistically significant results. The meta-analysis showed that high preoperative NLR is associated with worse survival in esophageal cancer, as shown in several solid tumors, but its use in the clinical practice is still underestimated. High-quality studies are needed to assess the most effective cut-off in survival prognostication and NLR relevance on postoperative complications.